Reference values for lung function: past, present and future - Stanojevic, S.; Wade, A.; Stocks, J. (The European respiratory journal, 2010)
Reliable interpretation of pulmonary function results relies on the availability of appropriate reference data to help distinguish between health and disease and to assess the severity and nature of any functional impairment. The overwhelming number of published reference equations, with at least 15 published for spirometry alone in the past 3 yrs, complicates the selection of an appropriate reference. The use of inappropriate reference equations and misinterpretation, even when potentially appropriate equations are used, can lead to serious errors in both under and over diagnosis, with its associated burden in terms of financial and human costs. Further misdiagnosis occurs when fixed cut-offs, such as 80% predicted forced expiratory volume in 1 s (FEV 1 ) or 0.70 FEV 1 /forced vital capacity, are used; particularly in young children and elderly adults. While per cent predicted has historically been used to interpret lung function results, z-scores are more appropriate as they take into account the predicted value, as well as the between-subject variability of measurements. We aim to highlight some of the main issues in selecting and using reference equations and discuss how recent developments may improve interpretation of pulmonary function results.